A comprehensive review on the utilization of biomaterials for bio-based hydrogel in therapeutic applications - Akter, Maria; Ros Azlinawati, Ramli (Springer Nature, 2024)
A bio-based hydrogel is a complex compound that consists of natural biomaterials and is widely applied for various therapeutic purposes. The modification from traditional biomaterials to reformulated bio-based hydrogels has gained a place at biomedical field due to the growth of therapeutic benefits such as drug delivery, tissue engineering, and regenerative medicine. Moreover, the increasing global demand for bio-based hydrogels has resulted in a worldwide shortage of mass formulations and has raised environmental awareness. By using natural biomaterials instead of synthetic ones, these hydrogels minimize their negative effects on the environment while simultaneously maximizing the successful execution of the product. However, the mechanisms governing degradation and bioactivity in bio-based hydrogels, which dictate drug release profiles, hydrogel stability, and therapeutic effectiveness, are not yet comprehensively understood. Therefore, by analyzing recent progress and ongoing challenges, this review will reveal how advanced bio-based hydrogels are quietly transforming the future of healthcare and offering novel solutions to pressing health problems.